2023
DOI: 10.1186/s12302-023-00721-8
|View full text |Cite|
|
Sign up to set email alerts
|

PFAS: forever chemicals—persistent, bioaccumulative and mobile. Reviewing the status and the need for their phase out and remediation of contaminated sites

Abstract: Background Per- and polyfluorinated alkyl substances (PFAS) have received increasing scientific and political attention in recent years. Several thousand commercially produced compounds are used in numerous products and technical processes. Due to their extreme persistence in the environment, humans and all other life forms are, therefore, increasingly exposed to these substances. In the following review, PFAS will be examined comprehensively. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 363 publications
0
34
0
Order By: Relevance
“…Remediation provides a 'solution' to contamination by treating land (or water) to remove toxins. In Aotearoa NZ, remediation of PFAS is both publicly and privately funded; remediation of PFAS overseas has proven to be expensive and often ineffective (Brunn et al, 2023). Efforts to remediate contaminated land focus on historic landfills and mining sites (Ministry for the Environment, 2022b).…”
Section: Remediationmentioning
confidence: 99%
“…Remediation provides a 'solution' to contamination by treating land (or water) to remove toxins. In Aotearoa NZ, remediation of PFAS is both publicly and privately funded; remediation of PFAS overseas has proven to be expensive and often ineffective (Brunn et al, 2023). Efforts to remediate contaminated land focus on historic landfills and mining sites (Ministry for the Environment, 2022b).…”
Section: Remediationmentioning
confidence: 99%
“…PFAS are a large group of synthetic chemicals containing a chain of linked carbon and fluorine atoms, which are widely used in consumer and industrial products. , Due to the high stability of the C–F bond, PFAS do not degrade easily in the environment, which leads to their environmental persistence and high bioaccumulation potential . Currently, more than 14 000 unique PFAS are listed in the CompTox Chemicals Dashboard of the United States Environmental Protection Agency (EPA), and this number is constantly increasing with the advancement of detection technologies and data processing methods.…”
Section: Use Of Ims and The Derived Ccs For The Analysis Of Ompsmentioning
confidence: 99%
“…Numerous studies showed that exposure to PFAS can lead to adverse health effects at the level of μg/L or less; , therefore, sensitive chemical analytical methods for PFAS are needed to support their further environmental fate and toxicity effect studies. The incorporation of IMS into a LC–MS/MS system can increase the S/N ratios of analytes by removing the background interferences; thus, lower limits of detection (LODs) can be obtained for the analytes. , Gonzalez de Vega et al utilized UPLC–TWIMS–QTOF to quantify the PFAS in Cooks River water and achieved LODs and limits of quantification (LOQs) of 0.19–0.76 μg/L and 0.56–2.30 μg/L, respectively.…”
Section: Use Of Ims and The Derived Ccs For The Analysis Of Ompsmentioning
confidence: 99%
“…5 Notably, PFAS at concentrations of a few μg L −1 or less accumulate in organisms, and are harmful to insects, aquatic fauna, and amphibians. 6 Photocatalysis is considered an efficient method widely used for the decomposition of various pollutants. 7 TiO 2 is the most frequently used photocatalyst, but it has shown insignificant activity for PFOA degradation, whereas In 2 O 3 and Ga 2 O 3 have yielded higher efficiencies.…”
Section: Introductionmentioning
confidence: 99%